2018
DOI: 10.4236/fns.2018.91003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pullulan and Hydrocolloids on Rheological Properties and Quality Parameters of Wheat-Soy Baladi Bread

Abstract: Baladi bread is a staple food in Egypt and high nutritive value however, stales rapidly. The aim of the study was to conduct a comparative evaluation of pullulan and hydrocolloid combinations on rheological properties and quality parameters of wheat-soy baladi bread. Pullulan polysaccharides (Pu) and hydrocolloids as Arabic gum (AG), K-carrageenan (KC), pectin (P), and xanthan gum (XG) were applied. Rheological properties of samples included Pu and hydrocolloids were analyzed through extensiograph and farinogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Overall, acacia performed better and controlled the dough softening by interacting with the gluten proteins by hydrogen bonding. Generally, the MTI and softening are positively correlated, where an increased MTI depicts an increase in the softening of the dough [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, acacia performed better and controlled the dough softening by interacting with the gluten proteins by hydrogen bonding. Generally, the MTI and softening are positively correlated, where an increased MTI depicts an increase in the softening of the dough [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar study reported that pullulan addition to bread dough tends to increase the extensibility, due to the water absorption ability of the pullulan and the protein content in it, that contributes to the elongation of the dough. [ 27 ] The extensibility of the dough decreased by 1.53 times with 10% gellan gum incorporation and increased by 1.39 times with 10% pullulan incorporation. The most important aspect of the polysaccharides with water is their role in plasticizing property.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] Pullulan with different hydrocolloids studied in baladi bread resulted in maximum dough extensibility via extensiograph and farinograph. [ 27 ] Gellan gum with 1–6% of incorporation showed a statistical significance whereas from 7–10% incorporation the extensibility was drastically reduced at p ≤ 0.05. This may be due to the gum property to break the network of gluten while dough kneading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baladi bread holds great importance in Egypt as a staple food. Efforts have been made to improve its quality and extend its shelf life, with research suggesting that the addition of hydrocolloids, such as pullulan, can enhance the dough properties and delay staling of baladi bread 1 . However, Consuming buckwheat has also been associated with the reduction of hyperlipidemia, blood pressure, and improved weight regulation.…”
Section: Introductionmentioning
confidence: 99%